Global Methamphetamine Trends: An Evolving Problem - Stoneberg, Danielle M. (International criminal justice review, 2018)
The methamphetamine (meth) problem is increasing in regions around the world. As the most widely manufactured amphetamine-type stimulant, it is the second most commonly used illicit drug worldwide. Outside of governmental sources, few studies have examined international meth patterns and trends. An analysis of secondary sources, including governmental and media reports, was conducted to examine recent shifts occurring internationally. Meth serves as an example of a global issue that continues to evolve and change over time. Recent indicators such as seizure statistics suggest that the problem is becoming complex and expansive. Manufacturing and trafficking activities are emerging in new areas and shifts in drug-related activities are occurring within and between countries around the world. This review describes global trends and changes in the problem internationally since 2010. The limitations of available sources of information are discussed.